CRISPR‐based gene drive in agriculture will face technical and governance challenges. (7th August 2017) - Gutzmann, Nicole; Elsensohn, Johanna E; Barnes, Jessica Cavin; Baltzegar, Jennifer; Jones, Michael S; Sudweeks, Jayce
Abstract : Comment on "Agricultural pest control with CRISPR‐based gene drive: time for public debate" by Courtier‐Orgogozo et al .